Analysis of Gross Motor Physical Development in the Traditional Ngada Game Wela Maka (Spinning Top Play) Activity among Group B Kindergarten Children - Karmelia Rofinda Meo Maku; Yanuarius Ricardus Natal (Universitas Pendidikan Ganesha, 2026)
Gross motor development is an important aspect of early childhood growth that needs to be stimulated through appropriate play activities. However, in practice, children are increasingly exposed to digital games, which reduces opportunities for physical activities that support motor development. This study aims to analyze the effect of the traditional game Ngada Wela Maka on early childhood gross motor development. This research used a quantitative approach with a quasi-experimental One Group Pretest–Posttest Design. The subjects consisted of 10 children selected through purposive sampling based on specific criteria. Data were collected using a gross motor development assessment sheet and analyzed using descriptive statistics and a Paired Sample t-test. The results show that children’s gross motor abilities improved after participating in the traditional game, covering all observed aspects, namely balance, movement coordination, large muscle strength, agility, and rhythmic coordination. These findings indicate that the Ngada Wela Maka traditional game has a significant effect in stimulating gross motor development in early childhood. In addition, this activity also supports children’s social development through cooperation, interaction, and discipline during play.The conclusion shows that traditional games are effective in optimally improving early childhood gross motor development. The implication of this study is that traditional games can be used as an effective, contextual, and enjoyable learning medium in early childhood education.